Efficacy of early transfusion of convalescent plasma with high‐titer SARS‐CoV‐2 neutralizing antibodies in hospitalized patients with COVID‐19. Issue 5 (26th March 2022) - Sanz, Cristina; Nomdedeu, Meritxell; Pereira, Arturo; Sauleda, Silvia; Alonso, Rodrigo; Bes, Marta; Brillembourg, Helena; García‐Vidal, Carolina; Millan, Anna; Martínez‐Llonch, Nuria; Pirón, María; Puerta‐Alcalde, Pedro; et al.
Abstract: Background: Despite most controlled trials have shown no measurable benefit of COVID‐19 convalescent plasma (CCP) in patients with COVID‐19, some studies suggest that early administration of CCP with high‐titer anti‐SARS‐CoV‐2 can be beneficial in selected patients. We investigated the efficacy of early administration of high‐titer CCP to patients with COVID‐19 who required hospitalization, Study design and methods: Observational, propensity score (PS) matched case–control study of COVID‐19 patients treated with CCP within 72 h of hospital admission and untreated controls from August 2020 to February 2021. All CCP donations had a Euroimmun anti‐SARS‐CoV‐2 sample‐to‐cutoff ratio ≥3. PS matching was based on prognostic factors and presented features with high‐standardized differences between the treated and control groups. The primary endpoint was mortality within 30 days of diagnosis. Results: A total of 1604 patients were analyzed, 261 of whom received CCP, most (82%) within 24 h after admission. Median age was 67 years (interquartile range: 56–79), and 953 (60%) were men. Presenting factors independently associated with higher 30‐day mortality were increased age, cardiac disease, hypoxemic respiratory failure, renal failure, and plasma d ‐dimer >700 ng/ml. After PS matching, transfusion of CCP was associated with a significant reduction in the 30‐day mortality rate (odds ratio [OR]; 0.94, 95% confidence interval [CI]: 0.91–0.98; p = .001) that extended to the 60th day after COVID‐19 diagnosis (OR: 0.95; 95% CI: 0.92–0.99; p = .01). Conclusion: Our results suggest that CCP can still be helpful in selected patients with COVID‐19 and call for further studies before withdrawing CCP from the COVID‐19 therapeutic armamentarium.